2009
DOI: 10.1007/s10665-009-9268-0
|View full text |Cite
|
Sign up to set email alerts
|

A model for reactive porous transport during re-wetting of hardened concrete

Abstract: A mathematical model is developed that captures the transport of liquid water in hardened concrete, as well as the chemical reactions that occur between the imbibed water and the residual calcium silicate compounds residing in the porous concrete matrix. The main hypothesis in this model is that the reaction product -calcium silicate hydrate gel -clogs the pores within the concrete thereby hindering water transport. Numerical simulations are employed to determine the sensitivity of the model solution to change… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…with D(w, ε) is water diffusivity and depends on both the moisture content and porosity (in general, we have that 0 ≤ w ≤ ε). A possible choice for diffusivity is Chapwanya et al (2009):…”
Section: Water Movementmentioning
confidence: 99%
See 1 more Smart Citation
“…with D(w, ε) is water diffusivity and depends on both the moisture content and porosity (in general, we have that 0 ≤ w ≤ ε). A possible choice for diffusivity is Chapwanya et al (2009):…”
Section: Water Movementmentioning
confidence: 99%
“…with A and B shape parameters for water diffusivity, suitable constants taken from Chapwanya et al (2009) and reported in Table 2.…”
Section: Water Movementmentioning
confidence: 99%
“…to describe the deviated water absorption [158,[163][164][165], but more information is needed on the kinetics of internal swelling and time-dependent transport properties of water in CBMs.…”
Section: Deviation From the Srt Lawmentioning
confidence: 99%
“…Physical swelling of C‐S‐H gels and evolving pore structure necessitate time‐dependent water transport properties. Several physical models have been proposed to describe the deviated water absorption, 158,163–165 but more information is needed on the kinetics of internal swelling and time‐dependent transport properties of water in CBMs.…”
Section: Detailed Connotations Of Water Sensitivitymentioning
confidence: 99%
“…In the literature, few studies have reported infiltration tests in concrete. One of the studies was reported by Chapwanya et al (2009), who modelled re-wetting experiments in concrete. They consist of placing dry concrete samples in a liquid bath and observing the progress of the wetting front.…”
Section: Introductionmentioning
confidence: 99%